Seroepidemiology of Helicobacter pylori in primary school students in Krotek, Cibeber Village, Serang District, Banten, Indonesia - Ratu Nurjanah; Pramita G. Dwipoerwantoro; Darlan Darwis (Indonesian Pediatric Society, 2009)
Background Helicobacter pylori infection is a common infection.Risk of infection in rural areas is six times higher than in urbanareas.Objectives To study the prevalence of H. pylori infection in primary school students in rural area and its contributing factors.Methods A cross-sectional study was performed in a rural primaryschool in Serang district, Banten, West Java. Serology of H. pyloriwas tested using Bio M pylori kit (Mataram, Indonesia).Results Forty two of 125 subjects (33.6%) had positive H. pyloriserologies. Bivariate analysis found that the the family habit ofeating together from one container increased the infection risk5.93 times (95% Cl 3.07 to 11.43). Source of drinking waterfrom common river increased the risk 9.88 times (95% CI 3.03to 32.24). Bed and bedroom sharing increased the risk 1.55 times (95% CI 1.23 to 1.95) and 2.22 times (95% CI 1.65 to 2.99), respectively. Multivariate logistic regression analysis including all variables with P <0.25 showed that the most significant factor contributing to H. pylori infection is common river as family drinking water source (OR 24.97, 95% CI 3.9 to 159.76), followed by family habit of eating together from one container (OR 10.23, 95% CI 3.05 to 34.27), and bed or bedroom sharing (OR 9.48, 95% CI 2.4 7 to 36.38).Conclusion Prevalence of H. pylori infection in rural schoolstudents is 33.6%. There are significant associations betweenH. pylori infection and family habit of eating together from onecontainer, bed sharing with other family members, and familydrinking water source from common river.